Preserving European paintings in Asian environment. The case of Goa Cathedral former altarpiece - Antunes, V (2018)
How to preserve a set of paintings made with European materials and taken to South Asia in the 16th century? A set of seven paintings belonging to the first altarpiece of Goa Cathedral now remain in its sacristy. Art history states that these paintings, assigned to the painter Garcia Fernandes, were produced in Lisbon circa 1530 and carried to Goa shortly after, Serrão (2011), Reis-Santos (1957). Presently, the conservation state of the paintings indicates urgent treatment. The most damaged paintings show significant loss of the original chromatic layer. This is mostly due to the high temperatures and relative humidity existing in tropical climates, such as Goa, different from the European. The Baltic oak support is covered with ground layers of calcium suphate, which present fissures and great losses due to the shrinkages of the wood support. The high reactivity of the ground materials to water is also a factor leading to specific material deterioration and degradation mechanisms. In comparison with the paintings of the same period produced in Portugal using the same materials, we verify a much higher degradation of the state of conservation. To access the procedures for preservation and restoration of this set of paintings we must take into account the possible degradation mechanisms of the constituent materials brought by specific environmental factors. This paper discusses the degradation problematic of this specific set of paintings taking into account their particular environment, while bringing results on the materials used. Concluding, this study will allow the knowledge on how to preserve and restore one of the most ancient sets of European paintings in India, kept since the 16th century in tropical climate.